Synthesis of hydrophilic HYNIC-[1, 2, 4, 5]tetrazine conjugates and their use in antibody pretargeting with 99mTc. Issue 29 (5th July 2018) - García, María Fernanda; Gallazzi, Fabio; Junqueira, Mara de Souza; Fernández, Marcelo; Camacho, Ximena; Mororó, Janio da Silva; Faria, Daniele; Carneiro, Camila de Godoi; Couto, Marcos; Carrión, Federico; Pritsch, Otto; Chammas, Roger; et al.
Abstract : Pretargeted imaging is shown to be an attractive strategy to overcome disadvantages associated with traditional radioimmunoconjugates. Abstract : Pretargeted imaging, based on the highly reactive process between [1, 2, 4, 5]tetrazines with trans -cyclooctene (TCO), appears as an attractive strategy to overcome disadvantages associated with traditional radioimmunoconjugates. To be successful, the radiolabeled component should react in vivo with the conjugated antibody and the non reactive excess clear fast from the organism. Herein, we explore the in vivo effects of hydrophilic linker incorporation into [1, 2, 4, 5]tetrazine systems bearing a 6-hydrazinonicotinyl (HYNIC) moiety for technetium-99m coordination. Incorporation of a polypeptide chain containing hydrophilic aminoacids, resulted in a derivative with renal clearance. Pretargeted bevacizumab imaging was used as proof of concept.